Toward Re-Entanglement: A Charter for the City and the Earth - Misselwitz, Philipp; Organschi, Alan (Bauhaus Earth Essays, 2024)
Recognizing the dire threats of climate collapse and mass extinction, the global initiative Bauhaus Earth convened a team of scientists, architects, spatial planners, and policymakers from around the world to author a manifesto. Toward Re-Entanglement: A Charter for the City and the Earth is a call for radical transformation. It challenges all those with a role in the conception, production, operation, and governance of the building sector to address the systemic ecological, climatic, and social impacts incurred by its activities. Twelve principles of "re-entanglement" guide the redesign of the entire life cycle of the urban realm: the reforming and rematerializing of the physical artifacts that comprise it, the reconfiguring of the socioeconomic structures that underpin it, and the reengaging of the bioregions that might sustainably supply it. In this way, the unprecedented convergence of the environmental and social crises we are causing offers powerful opportunities for systemic change.